Purification and renal effects of phospholipase A(2) isolated from Bothrops insularis venom - Machado Braga, Marcus Davis; Costa Martins, Alice Maria; Alves, Claudnio Diogenes; de Menezes, Dalgimar Beserra; Martins, Rene Duarte; Ferreira Barbosa, Paulo Sergio; de Sousa Oliveira, Isadora Maria; Toyama, Marcos Hikarl [UNESP]; Toyama, Daniela Oliveira; dos Santos Diz Filho, Eduardo Brito [UNESP]; Ramos Fagundes, Fabio Henrique [UNESP]; Fonteles, Manasses Claudino; et al. (Pergamon-Elsevier B.V. Ltd, 2008)
Bothrops insularis venom contains a variety of substances presumably responsible for several pharmacological effects. We investigated the biochemical and biological effects of phospholipase A(2) protein isolated from B. insularis venom and the chromatographic profile showed 7 main fractions and the main phospholipase A(2) (PLA(2)) enzymatic activity was detected in fractions IV and V. Fraction IV was submitted to a new chromatographic procedure on ion exchange chromatography, which allowed the elution of 5 main fractions designated as lV-1 to IV-5, from which lV-4 constituted the main fraction. The molecular homogeneity of this fraction was characterized by high-performance liquid chromatography (HPLC) and demonstrated by mass spectrometry (MS), which showed a molecular mass of 13984.20 Da; its N-terminal sequence presented a high amino acid identity (up to 95%) with the PLA(2) of Bothrops jararaca and Bothrops asper. Phospholipase A(2) isolated from B. insularis (Bi PLA(2)) venom (10 mu g/mL) was also studied as to its effect on the renal function of isolated perfused kidneys of Wistar rats (n = 6). Bi PLA(2) increased perfusion pressure (PP), renal vascular resistance (RVR), urinary flow (UF) and glomerular filtration rate (GFR). Sodium (%TNa+) and chloride tubular reabsorption (%TCl-) decreased at 120 min, without alteration in potassium transport. In conclusion, PLA(2) isolated from B. insularis venom promoted renal alterations in the isolated perfused rat kidney. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Bothrops insularis; phospholipase A(2); renal biological activity